Supplementation of enzymes and probiotics on body weight gain and protein metabolism in calves - Quisirumbay-Gaibor, Jimmy (2020)
The aim of this work was to evaluate the effect of Saccharomyces cerevisiae supplementation plus an enzyme complex (amylases, lipases and proteases) on daily body weight gain and blood urea level in Holstein Friesian calves from 5 to 61 days of age. The daily weight gain was 514 versus 462 g/day of the control group. The urea level was significantly higher in the experimental group (30.11 mg/dl) than in the control group (22.98 mg/dl) (p<0.01). It is concluded that dietary supplementation of S. cerevisiae and enzymes favors protein metabolism in calves, although it is not sufficient to produce an improvement in daily weight gain.